(3cJGH CSeGA Cgd HOQ GdTQjaI QVhGf Gddg Ydjge CLeYjfs - (3EHQGgje Mfja Hf eUWai, J(B1189(3g`s
(3ChdgG (B:s
(3eMeO Udi Gddg Ydjg hSde hTQa hcQe GHf YHO Gddg Hf YHO GdeWdH MQa GdCda CHj Hf cYH GdCNfS GdSdej GdCQbe Hf GdCQbe CSYO Hf jRjO CfS Hf eYGP CfS Hf bJGOIs
(3BNQgG (B:s
(3cbhdc adGf QVj Gddg Yfg Edi BNQg eG cdgG gcPG Gdefbhd HGdJhGJQ hGdCNHGQ hbO YdeJ eG jPcQ dc aj GdTQM Cf CWdbJ Ydjg hGddg CYdes
(3aj BNQg aGFOI ef cfR GdeYGQa , haGFOI CNQi aj GdCOYjI YfO gjGL CehGL GdHMQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 73s
(3gOjI GdYGQajf(B: 1 / 39s
(3EjVGM Gdecfhf(B: 1 / 80s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs